A Renovação do Currículo do Ensino Secundário no Brasil: as últimas batalhas pelo humanismo (1920-1960 - Souza, Rosa Fátima de [UNESP] (My University, 2009)
The text analyzes the debates put forward in the defense for a humanist curriculum in the Brazilian secondary schools me the period from 1920 and 1960. Basing on the articles published in the periodic of national circulating and texts by educators who problematize the question f humanism as the orientation guide for the curriculum, the text highlights the positions of the intellectuals connected to the Catholic Churcho beside the thoughts of the secondary school teachers and the intellectuals of the progressive tendency. The analyses also show how the humanism notion is going to be transformed along the twentieth century and how this notion was enrooted in the Brazilian culture.
Keywords: Curriculum; High School; History of Education